2023
DOI: 10.1002/clt2.12239
|View full text |Cite
|
Sign up to set email alerts
|

Association of asthma genetic variants with asthma‐associated traits reveals molecular pathways of eosinophilic asthma

Abstract: IntroductionAsthma is a complex, polygenic, heterogenous inflammatory disease. Recently, we generated a list of 128 independent single nucleotide polymorphisms (SNPs) associated with asthma in genome‐wide association studies. However, it is unknown if asthma SNPs are associated with specific asthma‐associated traits such as high eosinophil counts, atopy, and airway obstruction, revealing molecular endotypes of this disease. Here, we aim to identify the association between asthma SNPs and asthma‐associated trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, these results are not fully comparable with ours due to differences in the study population and age distribution and have not been replicated in other populations. In addition, other studies have identified SNPs in the IL18 receptor gene cluster and in the IL1 family that are linked to asthma-associated biomarkers (i.e., serum IgE, blood eosinophilic counts) in asthma or other allergic disorders [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these results are not fully comparable with ours due to differences in the study population and age distribution and have not been replicated in other populations. In addition, other studies have identified SNPs in the IL18 receptor gene cluster and in the IL1 family that are linked to asthma-associated biomarkers (i.e., serum IgE, blood eosinophilic counts) in asthma or other allergic disorders [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of this receptor in the CNS was suggested in many animal studies after CNS injury (in a mouse MCAO model [312]), after PNS injury (in mouse/rat CCI models [92,230]), and in diabetes in monkeys [314] and mice [315]. Furthermore, CCR4 has been shown to play an important role in the pathogenesis of many diseases in patients, such as TBI [309], asthma [316,317], dermatitis [318], and cancer [319]. The presence of CCR4 in the CNS [320,321] and PNS [186] suggests that CCR4 plays a role after injury; however, further studies are needed.…”
Section: Ccr4-ligands and Pharmacological Modulationmentioning
confidence: 99%
“…Interestingly, numerous SNPs linked to asthma onset and its characteristics have been identified [205]. SNPs in noncoding regions of the ORMDL3 gene lead to an increase in ORMDL3/ GSDMB expression that is associated with childhood-onset asthma [129,206] through the alteration of SL synthesis [207].…”
Section: Genomics and Transcriptomicsmentioning
confidence: 99%